Firm Value and Mandatory Risk Disclosure : An Empirical Investigation of Listed Companies Under Ind-AS107 in India - Gupta, Sushant; Singh, Gagandeep; Chandel, Ajay (Indian Journal of Finance, 2024)
Purpose : The purpose of this study was to investigate the relationship between mandatory risk disclosure practices and firm value in Indian-listed non-financial companies, considering the implementation of Ind-AS 107. The study aimed to analyze the impact of required risk disclosures on the valuation of the Indian listed firms and contribute to the understanding of risk reporting practices in the Indian context. Methodology : The study employed a panel data regression analysis using a fixed effect model. Data were collected from the NIFTY500 Index for the period from 2018–2022. A mandatory risk disclosure index was developed to assess the level of risk-related information provided by companies as per Ind-AS 107. Findings : The results indicated a significant positive relationship between mandatory risk disclosure practices and firm value in Indian-listed non-financial companies. The study revealed that companies with higher levels of mandatory risk disclosures tend to have higher valuations. Additionally, firm size was positively associated with firm value, while firm risk (leverage) was negatively correlated with valuation. Practical Implications : The study’s conclusions indicated that strengthening required risk disclosure procedures would have a favorable impact on Indian non-financial listed businesses’ valuation. These findings could be utilized by regulatory bodies and standard-setters to motivate businesses to provide more thorough and transparent risk-related data. This, in turn, may improve investor confidence, attract higher investments, and contribute to more informed decision-making. Originality : The study added to the body of knowledge by determining how the disclosure of required risk affected Indian enterprises’ valuation.